Fixed Point Results for Dualistic Contractions with an Application. (22nd January 2020) - Nazam, Muhammad; Mukheimer, Aiman; Aydi, Hassen; Arshad, Muhammad; Riaz, Raheel
Abstract : In this paper, by introducing a convergence comparison property of a self-mapping, we establish some new fixed point theorems for Bianchini type, Reich type, and Dass-Gupta type dualistic contractions defined on a dualistic partial metric space. Our work generalizes and extends some well known fixed point results in the literature. We also provide examples which show the usefulness of these dualistic contractions. As an application of our findings, we demonstrate the existence of the solution of an elliptic boundary value problem.